Institutional support and LMS implementation among academicians in vocational higher education - Lee Bih Ni; Li Liang; Cheng Haibao; Ji Dongli (RSIS International, 2025)
This study explores the influence of institutional support on the effectiveness of Learning Management System (LMS) implementation among academicians in vocational higher education institutions. Utilizing a mixed methods approach, the research combines primary quantitative and qualitative data collected online—with the aid of AI-assisted tools for data gathering and processing—with a secondary data analysis of institutional records, LMS usage logs, and related documentation. Findings reveal that institutional support, particularly in the form of technical assistance, professional development, and administrative policy, plays a critical role in shaping educators’ engagement with LMS platforms. The study highlights the importance of aligning institutional strategies with technological adoption to enhance teaching and learning outcomes in vocational settings.